With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Woman, native, other: writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press, 1989)
" . . . methodologically innovative . . . precise and perceptive and conscious . . . " —Text and Performance Quarterly "Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color." —Chandra Talpade Mohanty "The idea of Trinh T. Minh-ha is as powerful as her films . . . formidable . . . " —Village Voice " . . . its very forms invite the reader to participate in the effort to understand how language structures lived possibilities." —Artpaper "Highly recommended for anyone struggling to understand voices and experiences of those 'we' label 'other'." —Religious Studies Review Audio book narrated by Betty Miller. Produced by Speechki in 2021.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires